Application of a modified gaseous exposure system to the in vitro toxicological assessment of tobacco smoke toxicants. (2nd June 2014) - Breheny, Damien; Cunningham, Fiona; Kilford, Joanne; Payne, Rebecca; Dillon, Deborah; Meredith, Clive
<x xml:space="preserve">Abstract</x> Tobacco smoke is a complex mixture of over 6, 000 individual chemical constituents. Approximately 150 of these have been identified as 'tobacco smoke toxicants' due to their known toxicological effects. A number of these toxicants are present in the gaseous phase of tobacco smoke. This presents a technical challenge when assessing the toxicological effects of these chemicals in vitro. We have adapted a commercially available tobacco smoke exposure system to enable the assessment of the contribution of individual smoke toxicants to the overall toxicological effects of whole mainstream cigarette smoke (WS). Here we present a description of the exposure system and the methodology used. We use the example of a gaseous tobacco smoke toxicant, ethylene oxide (EtO), a Group 1 IARC carcinogen and known mutagen, to illustrate how this methodology can be applied to the assessment of genotoxicity of gaseous chemicals in the context of WS. In the present study we found that EtO was positive in Salmonella typhimurium strain YG1042, a strain that is sensitive to tobacco smoke. However, EtO did not increase the mutagenicity of the WS mixture when it was added at greatly higher concentrations than those found typically in WS. The findings presented here demonstrate the suitability of this exposure system for the assessment of the mutagenic potential of gases in vitro. Whilst we have focused on tobacco smoke toxicants, this system has broad application potential in studying the biological effects of exposure to a wide range of gaseous compounds that are present within complex aerosol mixtures. Environ. Mol. Mutagen. 55:662–672, 2014. © 2014 Wiley Periodicals, Inc.